Using mobile and fixed sensors for optimal monitoring of water distribution network under dynamic water quality simulations. (July 2022) - Shahmirnoori, Alireza; Saadatpour, Motahareh; Rasekh, Amin
Highlights: A water quality monitoring network (WQMN) is designed in water distribution network. WQMN aims to enhance the sustainability of water distribution networks (WDN). EPANET-MSX projected the dynamic water quality due to potassium cyanide injection. The contaminant detection time & contaminated water consumption are reduced in WQMN. The effects of mobile sensors' battery life & sink nodes' coverage area are studied. Abstract: Urban water distribution networks (WDNs) are strategic infrastructures, which have critical roles in preserving public health and social growth. This study designs a water quality monitoring network (WQMN) in the WDN Example 3 of EPANET2.0, contaminated with potassium cyanide (KCN), accounting for the dynamic changes of chlorine as a common water-quality parameter. The uncertainties in the contaminant events, such as the amount, location, start-time, and duration of contaminant injection, are considered in the problem formulations. A simulation-optimization framework based on EPANET-MSX and Particle Swarm Optimization algorithm is developed to determine the optimal location of the fixed sensor(s) and/or time and location of releasing mobile sensor(s). The results indicate that increasing the available mobile sensors from 1 unit to 3 or 5 units, decreased the contaminant detection time (DT) by 14% and 22%, increased the contaminant detection likelihood by 102% and 159%, and reduced the contaminated water consumption by 52% and 70%, respectively. The sensitivity analysis on the number of available sensors implies that changes in fixed sensors are more effective than mobile sensors on contaminant DT. The results showed the uncertainty in sink nodes' coverage area and mobile sensors' battery life become more important as the number of mobile sensors increases.